Odrabianie „lekcji (nie)obecności”, czyli o dziecięcej literaturze Holocaustu w metodyce nauczania polskiej kultury i literatury .......... 99 - Grossman, Elwira (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
UNDOING THE ‘LESSON OF ABSENCE’ OR COMMENTS ON TEACHING HOLOCAUST CHILDREN’S LITERATURE IN PROGRAMMES OF POLISH CULTURE FOR FOREIGNERS Inspired by Agnieszka Kania’s concerns expressed in her study Lekcja (nie)obecności. Dziedzictwo polsko-żydowskie w edukacji polonistycznej devoted to the absence of teaching Polish-Jewish heritage to students of Polish Language and Culture, Grossman undertakes the challenge of reviewing the existent Holocaust children’s literature (written in Polish) with the purpose of introducing it as a source for teaching Polish culture. Her overarching question is: ‘How to utilise literature addressing the Polish-Jewish heritage and the Holocaust in our Polish curriculum?’ In addressing this question, she draws on her own pedagogical experience of teaching the Holocaust and Polish-Jewish relations to foreign students as well as academic studies devoted to teaching children’s literature written by such scholars as P. Hunt, C. Butler, C. Leland, E. Arizpe, E. Finer, L. Kokkola (in English) and K. Zabawa, G. Lasoń-Kochańska, G. Leszczyński (in Polish). In her conclusion Grossman encourages academic teachers of Polish in Poland and abroad to reflect on the benefits of using the texts she discussed in their own practices as a valuable source for teaching inclusive thinking, mutual respect and understanding of cultural differences as well as cultural diversities in multilingual local communities of our global world.